Advanced HCC with amplified mesenchymal epithelial transition factor receptor responds well to savolitinib: a case report - Yan, Ningning; Zhang, Ziheng; Guo, Sanxing; Shen, Shujing; Li, Xingya (Frontiers in Medicine, 2023)
Objective Current treatment agents for HCC are mostly immune checkpoint inhibitors (ICIs) plus bevacizumab and multitarget tyrosine kinase inhibitors (TKIs); however, their limited overall response rate and shorter median progression-free survival (PFS) discourage their frequent use. The development of Mesenchymal Epithelial Transition Factor receptor (MET) Tyrosine Kinase Inhibitors (MET-TKI) has transformed the treatment pattern in MET-altered solid tumors and improved their prognosis. However, the benefits of MET-TKIs in MET-amplified hepatocellular carcinoma (HCC) remain unclear. Methods Here, we present a case of advanced HCC amplified with MET treated with savolitinib, a MET-TKI, after progression from first-line treatment with bevacizumab plus sintilimab. Results The patient achieved a partial response (PR) to savolitinib in the second line setting. The progression-free survival (PFS) of first-line of bevacizumab plus sintilimab and sequential second-line treatment with MET-TKI, savolitinib, are 3 and over 8 months, respectively. furthermore, the patient still had continuous PR status with manageable toxicities. Conclusions The present case report provides first-hand evidence that savolitinib may be beneficial for patients with advanced MET-amplified HCC and offers a promising treatment option.